Airborne pollutants collection and analysis based on their fluorescence spectral measurements: a case study on diesel exhaust combustion particles - Veaceslav Sprincean; Arcadi Chirita; Simion Astilean; Monica Focsan; Ana-Maria Craciun; Florentin Paladi (Discover Environment, 2024)
Abstract Collection of the airborne pollutants by using our prototyped device was followed by their analyses based on the performed fluorescence spectral measurements for three samples collected on the quartz substrates and on the surface of a silicon monocrystalline (opaque) wafer. Results for combustion particulate matter from diesel exhaust, including a comparison with air pollutants analysis for microparticles collected on a street in Chisinau city during rush hour, are presented. The strength of the proposed method represents the possibility to study directly the airborne solid microparticles collected on different substrates, and it is suitable for studying air pollution on large areas and at different altitudes by using unmanned aerial vehicles (UAVs). Microparticles fluorescence spectroscopy results indicate that the individual particles exhibit composite fluorescence spectra.